Transformasi Penggunaan Kitab Digital dalam Pelaksanaan Bahtsul Masail di Pondok Pesantren Al Luqmaniyyah Yogyakarta - Rangga Pratama Saputra; Zainal Arifin Ahmad; Muhammad Sabri; Zakiya Sifa Amri (PT Ininnawa Paramacitra Edukasi, 2026)
This study aims to analyze the transformation of digital kitab kuning usage in the implementation of bahtsul masail at Pondok Pesantren Al Luqmaniyyah Yogyakarta and its implications for knowledge transmission and scholarly authority within Islamic boarding schools. This research employed a qualitative approach using observation, interviews, and documentation techniques. The findings reveal that digital Islamic classical texts are utilized to accelerate reference searches, broaden access to classical literature, and improve the efficiency of deliberative forums. However, digital references remain under the epistemological supervision of ustaz through a verification mechanism of legal arguments. The study identifies a dual- authority pattern in which technology functions as a reference-search tool while ustaz maintain authority over interpretative validity. In addition, the research finds a cross-referencing hybrid practice combining digital and printed texts in legal analysis. These findings indicate that digitalization in pesantren represents not a shift away from tradition, but an epistemological adaptation that sustains Islamic scholarly traditions in the digital era.